Exploring and identifying leadership style, employees attitude and behavior in SMEs in Sabah - Arsiah Bahron; Jennifer Chan Kim Lian; Fumitaka Furuoka; Kalsom Ab. Wahab; Roslinah Mahmud (Universiti Malaysia Sabah, 2010)
The study aims to collect data on leadership style and entrepreneurial behavior among managers of SMEs in Sabah and the job satisfaction and organizational commitment among employees in the respective firms. At the first phase, a total of 500 questionnaires were distributed to the managers and only 52 were returned. At the second phase, each of the firms that responded in the first phase were sent 10 questionnaires each to be distributed to their employees. A total of 108 questionnaires returned by the employees. The research found that the managers scored high on the transformational leadership style in which all the dimensions have a mean score of more than 4.00 (idealized influence 5.94, inspirational motivation 4.82, intellectual stimulation 5.93, and individualized consideration 5.27). While on the transactional leadership style the mean scores of the dimensions are between 2.53 to 5.93. This is quite consistent with past research in which leaders in SMEs are expected to have high score on the transformational leadership dimensions. On the entrepreneurial behavior, the managers score relatively high on the mean score (all above 4.0) with extra effort having the highest (6.06) and risk taking the lowest (4.36). On the employees side, they score relatively high on the three dimensions of organizational commitment (majority of them above 3.0 out of 7.0). The level of satisfaction among them is also high with more then 94% score above 3.0 (out of 7.0). The discussion also cover the differences that exist between groups of managers and employees based on different demographic factors on the four variables measured.